The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1403998
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Finite Element Model of Tissue Electropermeabilisation

Abstract: Sequential model of liver tissue electropermeabilisation around two needle electrodes was designed by computing electric field (E) distribution by means of the finite element (FE) method. Sequential model consists of a sequence of static FE models which represent E distribution during tissue permeabilisation. In the model an S-shaped dependency between specific conductivity and E was assumed. Parameter estimation of S-shaped dependency was performed on a set of current measurements obtained by in vivo experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The extent of electroporation of cells accounts for the increase of the permeability in the cellular membrane and is directly related to the magnitude of the electric field, E , which in turn, can be computed as follows: E=||, where is the electric potential that can be calculated solving a Laplace‐type equation, given by ()σ=0. As the electroporation process leads to the formation of pores in the cellular membrane, the electric conductivity of that membrane increases as well. The effective electric conductivity, σ , that appears in (3) is estimated in terms of the magnitude of the electric field, E , using the relationship established in Šel et al: σ()E=σmaxσmin1+α.eEab+σmin, a=Erev+Eirrev2, b=EirrevErevβ, where α and β are sigmoidal function parameters determined in a combined experimental and computational study by Šel et al and E rev and E irrev represent the thresholds of E corresponding to reversible and irreversible electroporation, respectively. On the other hand, σ max and σ min are the maximum and minimum electric conductivities of the tissue, respectively, with σ max corresponding to the maximum threshold of σ due to the electroporation and σ min to electric conductivity without electroporation.…”
Section: Mathematical Modeling and Numerical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of electroporation of cells accounts for the increase of the permeability in the cellular membrane and is directly related to the magnitude of the electric field, E , which in turn, can be computed as follows: E=||, where is the electric potential that can be calculated solving a Laplace‐type equation, given by ()σ=0. As the electroporation process leads to the formation of pores in the cellular membrane, the electric conductivity of that membrane increases as well. The effective electric conductivity, σ , that appears in (3) is estimated in terms of the magnitude of the electric field, E , using the relationship established in Šel et al: σ()E=σmaxσmin1+α.eEab+σmin, a=Erev+Eirrev2, b=EirrevErevβ, where α and β are sigmoidal function parameters determined in a combined experimental and computational study by Šel et al and E rev and E irrev represent the thresholds of E corresponding to reversible and irreversible electroporation, respectively. On the other hand, σ max and σ min are the maximum and minimum electric conductivities of the tissue, respectively, with σ max corresponding to the maximum threshold of σ due to the electroporation and σ min to electric conductivity without electroporation.…”
Section: Mathematical Modeling and Numerical Methodsmentioning
confidence: 99%
“…On the other hand, D tissue , ε and μ R represent the effective diffusivity of the drug in the tissue, the porosity of the tissue and the mass transport coefficient, respectively. The calculation of μ R is carried out following the model proposed by Boyd and Becker, in which μ R is posed in terms of the magnitude of the electric field, E , and the time elapsed from the previous electroporation pulse ( t p ), as given by μR=DOER()E,t.()μmaxμmin+μmin, where μ max and μ min are the maximum and minimum membrane mass transfer coefficient, respectively while DOE R ( E , t ) is the transient degree of electroporation (DOE), which accounts for the transient resealing of reversibly electroporated cells and is computed as follows: DOER()E,t=italicDOE()E.[]()1italicDIE()E.etpτ+italicDIE()E, with τ as the permeability decay time coefficient and DOE is the degree of electroporation that takes into account the increase in the electric conductivity of the tissue as a result of electroporation, as given by italicDOE()E=σ()Eσminσmaxσmin. The time constant for cell permeability, τ , is dependent on the pulse characteristics. The constant used in this work was experimentally determined in, which used a pulse duration of 100 μs and is therefore the value considered here.…”
Section: Mathematical Modeling and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were unable to assume constant conductivity since it has been shown that conductivity of tissue increases more dramatically after electroporation than cells in suspension due to the large ratio of cell volume to extracellular fluid volume 25 . Ions leak out of the cells when they are electroporated 38 therefore increasing conductivity. Joule heating effects also increase conductivity and act as a volumetric heat source.…”
Section: Methodsmentioning
confidence: 99%
“…In using this function, we assumed that conductivity increases by a factor of three since this was reported for other organs during electroporation 38 . We must also account for metabolic heat generation, conduction and convection due to blood perfusion.…”
Section: Methodsmentioning
confidence: 99%